Democracy and human rights in Tanzania Mainland : the Bill of Rights in the context of constitutional developments and the history of institutions of governance - Wambali, Michael Kajela Beatus (1997)
This thesis is an examination of human rights and constitutional development in Tanzania Mainland. The colonial and post-colonial history is used to analyse the development of human rights struggles, as well as institutions such as the Bill of Rights in the recent development of multi-party democracy. The thesis intends to establish that in spite of global factors such as pressure for democratisation from international institutions, the achievement of the Bill of Rights in Tanzania Mainland is part of a wider rights struggle of the people of Tanzania. The effective legal and political implementation of specific rights such as the right to vote, freedom of association and assembly reflect the state of that struggle. The thesis further seeks to establish that while the government sponsored the enactment of the Bill of Rights in 1984 and the re-introduction of multi-partism in 1992, it has always preferred to exercise extreme control over the enjoyment of political rights. This has often involved curtailing the establishment and free operation of institutions of popular democracy. The thesis goes on to suggest that unless a democratic culture and civil society are restored in the country, the success of the rights struggles of the people will be far-fetched. Together with the above it is argued that the struggle for rights could be enhanced by working from what is provided as legal rights, all interested parties pushing for the expansion of the human rights field. This can only be attained if the majority of Tanzanians are made aware of the existence of such rights through legal literacy programs.